Genomic Selection: A Tool for Accelerating the Efficiency of Molecular Breeding for Development of Climate-Resilient Crops - Budhlakoti, Neeraj; Kushwaha, Amar Kant; Rai, Anil; Chaturvedi, K K; Kumar, Anuj; Pradhan, Anjan Kumar; Kumar, Uttam; Kumar, Rajeev Ranjan; Juliana, Philomin; Mishra, D C; Kumar, Sundeep (Frontiers in Genetics, 2022)
Since the inception of the theory and conceptual framework of genomic selection (GS), extensive research has been done on evaluating its efficiency for utilization in crop improvement. Though marker-assisted selection has proven its potential for improvement of qualitative traits that are controlled by one to few genes with large effects, its role in improving quantitative traits that are controlled by several genes with small effects is limited. In this regard, GS that utilizes genomic-estimated breeding values of individuals obtained from genome-wide markers to choose candidates for the next breeding cycle is a powerful approach to improve quantitative traits. In the past 20 years, GS has been widely adopted in animal breeding programs globally because of its potential to improve selection accuracy, minimize phenotyping, reduce cycle time and increase genetic gains. In addition, given the promising initial evaluation outcomes of GS for the improvement of yield, biotic and abiotic stress tolerance and quality in cereal crops like wheat, maize and rice, prospects of integrating it in breeding crops are also being explored. Improved statistical models that leverage the genomic information to increase the prediction accuracies are critical for the effectiveness of GS-enabled breeding programs. Study on genetic architecture under drought and heat stress helps in developing production markers can significantly accelerate the development of stress resilient crop varieties through GS. This review focuses on the transition from traditional selection methods to GS, underlying statistical methods and tools used for this purpose, the current status of GS studies in crop plants and perspectives for its successful implementation in the development of climate-resilient crops.